Magic Mushroom as a Danger Narcotics: a Case Study in Yogyakarta - Nursyah, Yufani Julia Nursyah; Tongat, Tongat; Erdianti, Ratri Novita; Al-Fatih, Sholahuddin (Hang Tuah Law Journal, 2024)
The research aims to train oneself to articulate scientific thoughts in writing so that knowledge, particularly legal knowledge, continues to develop. The research also focuses on the implementation of Law No. 35 of 2009 regarding legal action against the circulation and abuse of narcotics, specifically magic mushrooms, in Yogyakarta City, as well as the obstacles faced by the police's narcotics unit, the Sleman Police Department, the Investigation Division, and the National Narcotics Agency (BNN). This study employs a socio-legal approach and is analyzed using qualitative descriptive techniques. The primary data comes from interviews with the BNN and the police in the Yogyakarta region. Overall, this research emphasizes the importance of enhancing human resources, knowledge, and priorities in law enforcement related to the circulation and abuse of magic mushrooms in Yogyakarta. More effective and comprehensive law enforcement is needed to address this issue thoroughly. The research findings indicate the ambiguity of the legal status of magic mushrooms, the limitations of law enforcement resources, technical challenges in enforcement, a lack of prioritization in action, and the need for broader education and knowledge.